Comparison of K Nearest Neighbor Algorithm with Apriori Algorithm to Analyze Lifestyle Patterns in Hypertensive Patients - Steven Steven; Ricky Wijaya; Helbert Yawin; Saut Dohot Siregar (Jurnal Indonesia Sosial Teknologi, 2024)
Hypertension is one of the most influential cardiovascular diseases that can lead to organ disorders such as heart dysfunction or stroke and hypertension is often discovered by chance. This disease can interfere with the work of other organs if left untreated, especially the heart and kidneys. Not paying attention to diet, exercise, stress, smoking, and drinking alcohol can all be causes of increased risk of hypertension. To predict people with hypertension and find out the comparison of behavior and lifestyle patterns with hypertension patients using a priori algorithm in the case study of Sei Semayang Health Center. So the results of rapidminer use the apriori algorithm to analyze the Comparison of K the nearest Neighbor Algorithm with the apriori Algorithm to Analyze Lifestyle Patterns in Hypertensive Patients the results obtained is U1 which means there are people with hypertension aged 25-38 years who have more hypertension and the results are H2 which means that people have but do not control to the doctor with a pattern style such as consuming alcohol, Smoking, and lack of exercise, sugar consumption, consumption of saturated fat and foods that contain a lot of salt and rarely consume vegetables or fruits and foods containing MSG then more and more people who have hypertension with an unhealthy lifestyle.